The successful implementation of enterprise resources planning system: Influence of top management support, system quality, and business process reengineering - Anisa Risela Amanda; Firman (Operations Management and Information System Studies, 2021)
The purpose of this research is to study the impact of top management support, system quality and business process reengineering on the successful implementation of PT Semen Padang's enterprise resources planning (ERP) system. A questionnaire survey collected 100 respondents of the study. Using multiple linear regression, F-test and t-test, hypotheses were tried in order to simultaneously understand (mainly) the influence of the independent variable on the need variable at the confidence level (α=0.05). The results based on the t-test show that top management support and business process reengineering have a significant impact on the success of enterprise resource planning, while system quality has no significant impact on the success of enterprise resource planning.